Suppression of tumorigenicity in hybrids of normal and oncogene-transformed CHEF cells. - Craig, R W (1985)
Somatic cell hybridization experiments were carried out to determine whether normal cells have the ability to suppress the transforming effects of a defined oncogene. A nontransformed Chinese hamster embryo fibroblast cell line (CHEF/18-dm2) was used as the normal parent, and a CHEF/18 transfectant carrying the human mutant c-Ha-ras (EJ) oncogene was used as the tumorigenic parent. Selected hybrids (L318 cell lines) were assayed for the presence of EJ DNA, for the p21 product of the c-Ha-ras gene, and for various indices of cell transformation. These hybrids exhibited a fibroblastic morphology similar to the normal parent, although they contained the EJ gene and expressed its p21 protein product at levels comparable with the transformed parent. They had a reduced capacity for anchorage-independent growth (plating efficiency in methylcellulose of less than 0.3-13%, as compared with greater than 90% for the transformed parent) and decreased tumor-forming ability in athymic mice. These findings show that normal CHEF/18 cells contain suppressor genes capable of inhibiting expression of the transformed phenotype, and tumor-forming ability, in the presence of an activated EJ oncogene.